Murder road eaudiobook - St. James, Simone (Books on Tape, 2024)
A young couple find themselves haunted by a string of gruesome murders committed along an old deserted road in this terrifying new novel from the New York Times bestselling author of The Book of Cold Cases . July 1995. April and Eddie have taken a wrong turn. They’re looking for the small resort town where they plan to spend their honeymoon. When they spot what appears to a lone hitchhiker along the deserted road, they stop to help. But not long after the hitchiker gets into their car, they see the blood seeping from her jacket and a truck barreling down Atticus Line after them. When the hitchhiker dies at the local hospital, April and Eddie find themselves in the crosshairs of the Coldlake Falls police. Unexplained murders have been happening along Atticus Line for years and the cops finally have two witnesses who easily become their only suspects. As April and Eddie start to dig into the history of the town and that horrible stretch of road to clear their names, they soon learn that there is something supernatural at work, something that could not only tear the town and its dark secrets apart, but take April and Eddie down with it all.